The Influence of Motivation and Work Discipline on Employee Performance Through Job Satisfaction As an Intervening Variable (Study at PT.Branky Bumi Asri) - Danis Martifa; Heni Susilawati (ProBisnis : Jurnal Manajemen, 2023)
Work quality will increase when employees are able to do tasks in line with their skills and the nature of the position they hold. Using job satisfaction as a mediator, this study will analyze how employee motivation and work discipline affect performance and happiness at PT Branky Bumi Asri. This research uses a quantitative strategy based on a survey sent to all 58 workers of PT Branky Bumi Asri. Total sampling is employed, and Likert-scale questionnaires are utilized to obtain primary data. Multiple linear regression, hypothesis testing, the Sobel test, and checks for validity and reliability are all part of the data analysis process. Employee performance at PT. Branky Bumi Asri was shown to be highly influenced by employees' levels of motivation and work discipline. The importance of job happiness as a mediating variable shows the interconnectedness of motivation and work discipline with employee performance within the framework of the organization's work environment.